Three-Dimensional Changes of the Auditory Canal in a Three-Year Period during Adolescence Using CBCTs - Adam Woods; Manuel O. Lagravère (International Journal of Dentistry)
Purpose. There is a lack of identifying suitable regions in the head that can be used for three-dimensional superimposition techniques. For this reason, with the use of cone-beam computed tomography (CBCT), the ear canals were analyzed to verify changes during a period of three years in the adolescent years. Methods. CBCTs from fifty-six patients (ages: 10 to 20) were used to landmark the anatomy of the ear canals. Each patient was analyzed using two CBCT reconstructions that were taken approximately three years apart. AVIZO® software was used to locate 28 landmarks distributed following the ear canal path and foramina (ovale, spinosum, rotundum, etc.) in the cranial base to obtain spatial relationships. Three-dimensional coordinates were obtained from the landmarks, and the average distance between various landmark pairings was calculated. The repeated measure ANCOVA was used to determine statistical significance. Results. In the main data set, the largest mean distance change was found to be 4.37 mm ±  18.29 mm between the left foramen ovale and the left superior medial ear canal opening. The smallest mean distance change was 0.18 mm ± 3.25 mm between the right inferior lateral ear canal opening and the right inferior medial ear canal opening. Conclusions. During the adolescent years, the ear canal presents dimensional changes. Even though in different areas throughout the canal, the average distances were minor, still, large standard deviations were present; thus, caution should be taken when trying to use this structure for superimposition of CBCTs.